Research in organizational change and development. Vol. 17 - Woodman, Richard W.; Pasmore, William A.; Shani, Abraham B. (Research in organizational change and development,, 2009)
Research in Organizational Change and Development is an annual publication devoted to thoughtful studies and ground breaking theoretical work dealing with the topic of change in organizational settings. The series serves to showcase the latest approaches to organizational research, whether they be quantitative or qualitative in nature. Some of the papers in Volume 17 bring new perspectives to classic issues in the field such as resistance and communication. Others explore new territories, such as activating neural mechanisms to create more sustainable change. The series has been around long enough to substantiate the claim that we have published some true classics in the field of organization development and change. While it's too early to say whether the papers in Volume 17 contain new classics, there are certainly some interesting and worthwhile pieces to read that have the potential to become classics at some time in the future. Research in Organizational Change and Development will continue to serve the mission of stimulating thinking that can make a significant difference in organizational outcomes that matter to our future.